2016
DOI: 10.1515/jomb-2016-0009
|View full text |Cite
|
Sign up to set email alerts
|

Association of GSTO1 and GSTO2 Polymorphism with Risk of End-Stage Renal Disease Development and Patient Survival

Abstract: SummaryBackgroundOxidative stress in patients with end-stage renal disease (ESRD) is associated with long-term cardiovascular complications. The cytosolic family of glutathione S-transferases (GSTs) is involved in the detoxication of various toxic compounds and antioxidant protection. GST omega class members, GSTO1 and GSTO2 possess, unlike other GSTs, dehydroascorbate reductase and deglutathionylation activities. The aim of this study was to clarify the role of genetic polymorphisms of GSTO1 (rs4925) and GSTO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Among the most common causes of CKD and progression to ESRD are diabetes mellitus (DM) (33% of adult CKD cases) and arterial hypertension (HTA) (21% of adult CKD cases) ( 9 , 10 ). The reason is a constant rise in the number of these patients which is »a medical catastrophe of world-wide dimensions« (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Among the most common causes of CKD and progression to ESRD are diabetes mellitus (DM) (33% of adult CKD cases) and arterial hypertension (HTA) (21% of adult CKD cases) ( 9 , 10 ). The reason is a constant rise in the number of these patients which is »a medical catastrophe of world-wide dimensions« (11) .…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have investigated GSTO2 polymorphisms in non-malignant diseases. Cimbaljevic et al reported that individuals with the variant GSTO2 *GG genotype were at higher risk of ESRD development compared to carriers of the GSTO2 *AA genotype [ 49 ]. In our study, we found that individuals with the GSTO2 *AG genotype were more prone to symptomatic diabetic nephropathy development in comparison to the carriers of the wild-type GSTO2 *AA genotype.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL10 [76], SIGLEC1 [77] and IL1R2 [78] have been suggested to be associated with neurological diseases. CXCL9 [79], SIGLEC1 [80], IL1R2 [81], KLF15 [82] and CD207 [83] [146], STAT4 [147], CXCL8 [148], KLF2 [149], ADM (adrenomedullin) [150], EGR1 [151], TRIB1 [152], SOD2 [153], OXSR1 [154], IL6R [155], CD44 [156], LRG1 [157], PFKFB2 [158], PACSIN2 [159], MYH9 [160], DOT1L [161], CXCL16 [162], PTEN (phosphatase and tensin homolog) [163], FOXO3 [164], DDIT4 [165], PINK1 [166], IQGAP1 [167], ADIPOR1 [168], MTMR3 [169], USF2 [170], SGK1 [171], GSTO2 [172], ETS2 [173], TKT (transketolase) [174], CMIP (c-Maf inducing protein) [175], THBD (granzyme A) [464], IFNG (interferon gamma) [465], IFIH1 [466], STAT1 [467], CCR5 [468], ADCY5 [469], MT2A [470], DPP4 [471], FASLG (Fas ligand)…”
Section: Discussionmentioning
confidence: 99%